Hyophorbe lagenicaulis, Bottle Palm - Melissa H. Friedman; Michael G. Andreu; Heather V. Quintana; Mary McKenzie (EDIS)
FOR 245, a 2-page fact sheet by Melissa H. Friedman, Michael G. Andreu, Heather V. Quintana, and Mary McKenzie, describes this palm with a bottle shaped trunk that is endemic to the Mascarene Islands east of Madagascar, and can grow in south Florida — scientific and common names, description, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.